Analisis Hubungan Antara Kebersihan Lingkungan Permukiman dengan Kesehatan Masyarakat - Ulyani, Nadiyya (Maliki Interdisciplinary Journal, 2025)
This research explores the link between residential environmental cleanliness and public health. Clean surroundings are crucial in preventing environment-related diseases such as diarrhea, dengue fever, and skin infections. The study reveals that effective waste management, proper sanitation, and organized drainage systems are associated with lower disease prevalence. Promoting healthy behavior and ensuring adequate sanitation facilities significantly enhance community health. The findings affirm that maintaining residential environmental cleanliness is a fundamental requirement for establishing a healthy society. Based on these results, this study recommends the need for synergy between the government, communities, and relevant stakeholders in efforts to sustainably improve residential environmental cleanliness. Policy interventions focused on health education, improving sanitation infrastructure, and strengthening community participation are expected to reduce the burden of disease and improve overall well-being. Thus, environmental cleanliness should be viewed not only as a physical aspect but also as a long-term investment in public health development.